Energy Use Pattern and Future Energy Requirement for Crop Production by 2020 - De, Dipankar (Journal of Agricultural Engineering, 2006)
India achieved rise in food grains productivity from 872 kg/ha ( 1970) to 1707 kg/ha (2003) requiring energy use of 5440 MJ/t in 1970 to 11391 MJ/t in 2003. The direct commercial/indirect energy ratio increased from 0.16 in 1970 to 1.74 in 2003, reflecting increasing role of mechanisation. Among fOOd grain crops, wheat and paddy are high-energy consumers. The oilseed crops consume lower energy. Sugarcane and potato are high-energy consumers. Generally, less than 15 % of Indian farms efficiently use their resources. Traditional areas have higher scope of increasing energy efficiency than the others. Improved cultivation practies with optimal resource Uses can further improve energy efficiency. Highest energy productivity is obtainable at yields lower than the potential. Farm power requirement would be at least 2kW/ha, mechanical power contributing the maximum. With better energy management practices adopted in some areas, at least 25% of additional energy demand can be met out of the present consumptions.